THE USE OF TRADITIONAL REPETITION IN THE EPIC "TAHIR AND ZUHRA" (ResearchJet Journal of Analysis and Inventions, 2021)
The article focuses on several variants of the Uyghur version of the epic "Tahir and Zuhra" and provides information about the traditional trinity in the epic. Unlike other versions of the epic "Tahir and Zuhra" in the folklore of the Turkic peoples, the "Kashgar variant" of this epic, which is an example of Uyghur folklore, uses one of the most important structural and semantic models of the epic plot - the traditional "trinity".